PENGARUH PARTISIPASI DALAM PENYUSUNAN ANGGARAN, STRUKTUR DESENTRALISASI, DAN TEKNOLOGI INFORMASI TERHADAP KINERJA MANAJERIAL (STUDI PADA SKPK BANDA ACEH) - Irzan, Mulya; Abdullah, Syukriy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The purpose of this research is to test participation effect in arranging budgets, decentralization structure, and information technology for managerial performance (studies in work unit set in Banda Aceh). Population in this research is the work unit set of Banda Aceh). Total populations are 38 SKPK (76 respondents). The methodology of this research is using questioner. The result of this research is to show that partially and simultaneously, participation in arranging budget, decentralization structure and information technology affect managerial performance